Localización geográfica de los servicios de salud en un subsistema de asentamientos rurales del Estado de México : un intento de evaluación - Garrocho, Carlos (El Colegio de México A.C., 1990)
This article renders the first outcomes which constitute the advances achieved in a study that intends to evaluate the efficiency of the location of health services of the Instituto de Salud del Estado de México (Health Institute of the State of Mexico). This is accomplished by means of a mathematical model that determines the site where the services should be offered in order to minimize the total and average distances the service users will have to cross. These outcomes will later on be compared with the real locations of the health services.